Unilateral Thoracoscopic Thymectomy for Thymoma: Does Side Matter? A Single Institutional Experience - Tamburini, Nicola; D'Urbano, Francesco; Bagolini, Francesco; Trapella, Giulia Salerno; Quarantotto, Francesco; Cavallesco, Giorgio; Maniscalco, Pio (The Thoracic and Cardiovascular Surgeon, 2021)
Background Thoracoscopic thymectomy is increasingly performed for the treatment of early stage thymoma. It is characterized by shorter postoperative hospital stay, decreased intraoperative blood loss, and fewer complications compared with transsternal thymectomy. Unilateral video-assisted thoracic surgery (VATS) thymectomy can be easily performed from either side of the thorax, because thymus is located in the middle of mediastinum. However, the side that provides better outcomes remains controversial. The purpose of this study was to compare the efficacy of right and left approaches in performing unilateral thoracoscopic thymectomy for thymoma.Methods Consecutive patients affected by thymoma who underwent VATS thymectomy on either side between February 2001 and March 2020 were enrolled in the study. Clinicopathologic, surgical, and oncological outcomes were retrospectively analyzed and compared among the two surgical approaches.Results Unilateral VATS approaches were performed on 29 patients: 12 (41%) on the left side and 17 (59%) on the right side. The mean age was 63.1 ± 11.3 years and the female/male ratio was 1.73:1. The mean operative time and the hospital stay for the left-side VATS and right-side VATS groups were, respectively, 168 ± 49.5 versus 171 ± 47.9 minutes (p = 0.9) and 3 ± 1.03 days versus 3.65 ± 1.93 days (p = 0.7). Postoperative complications occurred in one patient (3%) for left-side VATS group and one patient (3%) for right-side VATS. The 5-year disease-free survival was comparable between two groups (p = 0.74).Conclusion Unilateral VATS thymectomy in patients with thymoma can be safely and effectively performed by experienced surgeons in either side of the thorax with equivalent oncological outcomes.
Keywords: myasthenia gravis; VATS; thymectomy; outcomes; thymoma